Використання ринкових джерел фінансування дефіциту державного бюджету в Україні - Вергелюк, Юлія Юріївна; Verheliuk, Yuliia Yuriivna (Національний університет «Острозька академія», 2022)
Прийняття бюджету із дефіцитом в сучасному світі не вважається негативним явищем. Проте, обов’язковою умовою є визначення джерел фінансування такого дефіциту. В цьому руслі, використання ринкових джерел фінансування дефіциту державного бюджету – найоптимальніше. Розглянуто існуючі джерела фінансування дефіциту державного бюджету. Виокремлено ринкові джерела та визначено переваги їх використання. Проаналізовано передумови виникнення дефіциту Державного бюджету України. Проведено оцінку використання ринкових джерел фінансування дефіциту бюджету в Україні в розрізі позик на внутрішньому та зовнішньому ринках. За допомогою ряду індикаторів проведено оцінку наслідків використання ринкових джерел фінансування дефіциту Державного бюджету в Україні.

Adopting a budget with a deficit in the modern world is not considered a negative phenomenon. However, it is imperative to identify sources of funding for such a deficit. In this regard, the use of market sources of financing the state budget deficit is the most optimal. The purpose of the article is to reveal the theoretical provisions and practice of financing the state budget deficit of Ukraine with the help of market sources. The article solves the following tasks: determining the place of financing the budget deficit in the process of equalization using different sources; characterization of existing sources of financing the budget deficit, and establishing criteria for classifying them as "market"; analysis of statistics on the preconditions for the state budget deficit in Ukraine; assessment of the use of market sources of financing the state budget deficit of Ukraine and the consequences of such financing. The existing sources of financing the state budget deficit are considered, among which: deficit financing emission, tax sources, budget sequestration, sale of budget assets, internal state loans, external state loans, free assistance. Market features identify the sources related to the use of debt financing instruments of the budget deficit, namely internal and external government loans. The advantages of using market sources of financing the state budget deficit are determined, namely: non-inflationary nature, efficiency of coverage, possibility to choose the most optimal offers on the market, wide opportunities for diversification, large base of risk reduction mechanisms, high liquidity. An assessment of the market sources use in terms of the state budget deficit financing in Ukraine allowed us to establish that external financing, which carries the greatest burden on the budget, accounts for the majority. In the structure of external financing, the largest share belongs to loans received by Ukraine from international financial institutions. Sold foreign government bonds also account for a large share of external debt. The domestic market for deficit financing is realized through the sale of domestic bonds. The increase in domestic and external debts poses a threat to Ukraine's debt security, which was analyzed using a number of indicators.
Using market sources for financing the state budget deficit in Ukraine
Keywords: державний бюджет; дефіцит державного бюджету; джерела фінансування; державні позики; ринкові інструменти; state budget; state budget deficit; sources of financing; government loans; market instruments